Analysis of the Effect of Marketing Mix on Purchase Decisions and Impact on Consumer Loyalty at Chocolate Houses in Palu City - Multazam, Multazam; Jusni, Jusni; Munir, Abdul Razak (Technium Business and Management, 2022)
The purpose of this study is to analyze the effect of marketing mix variables on purchasing decisions, the influence of marketing mix variables on consumer loyalty, and the influence of marketing mix variables on consumer loyalty through purchasing decisions. The type of research used is descriptive research with a quantitative approach. The population in this study were all customers who had visited and made purchases of Central Sulawesi Chocolate at Rumah Cokelat. The sample used was 45 respondents who were taken using Cohen's formula. The data analysis used is descriptive analysis and path analysis. The results of the analysis show that the variables that have a positive and significant effect on purchasing decisions for Central Sulawesi chocolate products are price, place, and promotion, while those that are not significant are products, with p-value (p <0.05). The variables that have a positive and significant effect on consumer loyalty are product and price, while those that are not significant are place, promotion and purchasing decisions, with a p-value (p <0.05). And the variables that have a positive and significant effect on consumer loyalty through the intervening variables are price and promotion, while those that are not significant are products and distribution channels.